Case Report: Successful Management of Refractory Keratomycosis in an Alpaca Using Penetrating Keratoplasty and Combination Antifungal Therapy (Caspofungin 0.5% and Terbinafine 1%) - Foote, Braidee C.; Smith, Joe S.; Bowden, Anna Catherine; Allbaugh, Rachel A.; Sebbag, Lionel (Frontiers in Veterinary Science, 2021)
Fungal keratitis is a common disease in certain parts of the world and affects several species, including equids, camelids, and homo sapiens, leading to blindness or loss of the eye if the infection is not adequately controlled. Reports of clinical use of antifungals caspofungin and terbinafine are limited across both veterinary and human medical literature. The alpaca presented in this case demonstrates that deep keratomycosis can be caused by Scopulariopsis brevicaulis and Fusarium verticillioides, two previously unreported fungi to cause keratomycosis in camelids. This report demonstrates successful management with a combination of surgery and topical ophthalmic treatment with caspofungin 0.5% solution and terbinafine 1% dermatologic cream, after initially failing treatment with topical voriconazole 1% solution. Combination therapy appears more effective than monotherapy with some fungal organisms, and synergy between antifungal agents is thought to play a role in the success of combination therapy. Surgery to remove the bulk of the fungal infection is especially helpful in cases that fail initial medical therapy.